The Growing Phenomenon of ‘Frozen’ Virus Genome Sequences and Their Likely Origin in Research Facility Escapes - Steven E. Massey (Microorganisms)
‘Frozen’ virus genome sequences are sampled from outbreaks and have unusually low sequence divergence when compared to genome sequences from historical strains. A growing number of ‘frozen’ virus genome sequences are being reported as virus genome sequencing becomes more common. Examples of ‘frozen’ sequences include the 1977 H1N1 ‘Russian’ flu; Venezuelan Equine Encephalitis Virus from Venezuela and Colombia in 1995; E71 sequences from a Hand, Foot and Mouth outbreak in 2007–2009 in China; and a polio strain isolated in 2014 from Anhui, China. The origin of these ‘frozen’ sequences has been attributed to escapes from research facilities and often appears to be associated with vaccine work. Consequently, a new paradigm for pathogen emergence appears in operation, that involves laboratory research or vaccine production which utilizes ‘live’ virus isolates of historical strains. The accidental release and re-emergence of such strains are straightforward to detect from their genome sequences and should spur the routine sequencing and publication of all known pathogenic viral strains undergoing experimentation, or being used for vaccine manufacture, in order to facilitate tracing. However, it is noted that novel pathogenic viruses accidentally released into the population from research facilities are harder to detect if their sequence has first not been made public, which should prompt the routine sequencing and reporting of all novel pathogenic viruses before experimentation.